Surgical Ethics and Medicolegal Aspects - An Ayurvedic Persepective (International Journal of Ayurveda and Pharma Research, 2023)
Surgical ethics is an essential component in the practice of specting human rights and equality. “Principlism" is an approach in Bioethics which includes Autonomy, Beneficence, Non-maleficence and Justice. In the Ayurvedic classics ethical concepts are ever-present and an ethical under stream runs through all the texts. The essence of ethics is very well described in the textbooks of Ayurveda in the form of Chatushpada, Vaidya Guna, Sadvritta and Yogya. Concept of high level ethical surgical practice was there in the time of Susrutha Acharya, which is still now applicable in the era of modern surgery. This article gives a comprehensive analysis of the surgical ethics and medico legal aspects described in Ayurveda.